Patient selection and pathological outcomes using currently available active surveillance criteria. (7th June 2013) - El Hajj, Albert; Ploussard, Guillaume; de la Taille, Alexandre; Allory, Yves; Vordos, Dimitri; Hoznek, Andras; Abbou, Claude Clément; Salomon, Laurent
Abstract : Objectives: To establish the rate of higher risk criteria in various definitions of an active surveillance population. Patients and Methods: Over a period of 10 years, 1161 patients were diagnosed with prostate cancer and underwent radical prostatectomy at our institution. Statistical analysis was performed comparing the rates of upgrading, extracapsular extension, seminal vesical involvment and unfavourable disease (Gleason score upgrading >6 and/or T3 disease) for six groups of patients eligible for the University of Toronto, Royal Marsden, John Hopkins, University of California San Francisco, Memorial Sloan Kettering Cancer Center and Prospective Randomized International Active Surveillance. Results: Active surveillance protocols including patients with biopsy Gleason score 3+4 (Royal Marsden) had significantly higher rates of extracapsular extension ( P = 0.009), upgrading to pathological Gleason >3+4 ( P = 0.004) and unfavourable disease ( P = 0.001) compared to the most stringent John Hopkins criteria. Unfavourable disease was found in more than 40% of patients in all series with no significant difference between the Gleason 6 protocols. Biochemical recurrence‐free survival at 5 and 10 years was 76.7% and 63.3% for the entire cohort. Positive margins ( P < 0.001), pT3 tumours ( P = 0.006) and unfavourable disease ( P < 0.001) were significant predictors of biochemical recurrence. Conclusions: Active surveillance in patients with Gleason 3+4 presents a risk of missing unfavourable disease and should be limited to older patients with comorbidities. The differences in inclusion criteria between Gleason 6 protocols did not have a significant impact on the pathological results.